Occidental mythology . - Campbell, Joseph (London : Souvenir, 2001)
"In this third volume of The Masks of God - Joseph Campbell's series on comparative mythology - the preeminent mythologist examines the common themes and historical development of the pagan religions of Greece, Rome, and the Celts, along with the major monotheistic religions of the West (Zoroastrianism, Judaism, Christianity, and Islam)"--
Keywords: Mythology